"Jeannette Armstrong and her Feminism of Decolonisation" - Amante, Susana (2013)
Jeannette Armstrong, an Okanagan from Canada, is both a teacher and a writer. Her novel, Slash, has been much criticised by feminists, because of its male protagonist. By assuming a male perspective in her novel, this Native Canadian did not intend to legitimise and reinforce patriarchal power; rather, she argues that her choice was inextricably linked to a time when machismo and the European notion of leadership ruled the day. She further advances a philosophical reason: she wanted Native peoples to reconcile themselves with their traditional worldview, one which regarded masculinity and femininity not as opposites, but as synergistic; their relationship should be one of balance, reciprocity, complementarity and responsibility. Taking Slash into consideration, then, I intend to prove, together with the Okanagan author that, despite criticism, her novel is feminist and empowering, though not in a conventional sense: a different kind of feminism is here at stake—a feminism of decolonisation.